To compare the effectiveness of different mouthrinses on Streptococcus mutans count in caries active children - Aakansha Sharma; Nidhi Agarwal; Ashish Anand; Zohra Jabin (Elsevier, 2018)
Introduction: Streptococcus mutans is the prime microbe responsible for caries. Mouthwashes represent an effective means for decreasing their count. To ascertain this, three commercially available mouthrinses were evaluated for their antimicrobial activity. Materials and method: Chlorhexidine, Sodium fluoride and Herbal mouth rinse were evaluated for their efficacy against S. mutans in 60 children aged 6-12 years old. Plain water acted as the control group. Results: The values obtained were subjected to statistical analysis. ANOVA test, student-t test and paired t-test were used for evaluation. Chlorhexidine and fluoride showed statistically significant reduction in S. mutans count as compared to herbal rinse. Conclusion: All the mouthrinses used in the present study have shown a definite decline in S. mutans count.